"The Being Together of Strangers": Dionne Brand’s Politics of Difference and the Limits of Multicultural Discourse - Smyth, Heather (Studies in Canadian Literature, 2008)
Indigenous, racialized, and diasporic thinkers have long challenged the circumscription of "the national" as a frame for cultural and political identifications within Canadian space, privileging instead the trans- or subnational. Theorists like Smaro Kamboureli, Iris Marion Young, and Diana Brydon have shown how cultural products are firmly entangled with the national imaginary and are therefore capable of resisting it. The theoretical frameworks requisite for understanding this phenomenon need to account for various forms of difference, especially class, gender, and sexual orientation. Dionne Brand’s novel What We All Long For (2005) offers a vocabulary and poetics for how differences and alliances can crosscut foundational identity categories in unexpected ways. Brand offers an urban, cosmopolitan vision of a politics of difference that transcends the limits of multicultural discourse, creating fictional cities where, in Young’s phrase, difference is fostered through "the being together of strangers."